2022
DOI: 10.1186/s12888-022-03816-3
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the MIND dietary pattern and sleep quality, sleep related outcomes and mental health in male adults: a cross-sectional study

Abstract: Background A large number of studies have investigated the association of the Mediterranean and DASH diets with psychological health as well as sleep related outcomes. However, only a few number of studies have examined the association of their newly proposed hybrid, Mediterranean-DASH Intervention for Neurodegenerative Delay (MIND) dietary pattern, with sleep quality and sleep related outcomes. Methods This cross-sectional study was conducted on 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…While the MIND diet has been associated with slower decline in cognitive abilities 46 , and found to be more predictive of slowing cognitive decline than either the DASH or Mediterranean diets 13,47 , we did not find any correlation between the MIND diet and mood. This finding is in line with two previous studies in adults in their 30s, which also did not find any relationship between adherence to the MIND diet and reduced risks of stress, anxiety and depression 48,49 . However, a prospective cohort study in adults in their late 70s found that the MIND diet score was associated with lower rates of depression over a 6.5 years of follow-up 50 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While the MIND diet has been associated with slower decline in cognitive abilities 46 , and found to be more predictive of slowing cognitive decline than either the DASH or Mediterranean diets 13,47 , we did not find any correlation between the MIND diet and mood. This finding is in line with two previous studies in adults in their 30s, which also did not find any relationship between adherence to the MIND diet and reduced risks of stress, anxiety and depression 48,49 . However, a prospective cohort study in adults in their late 70s found that the MIND diet score was associated with lower rates of depression over a 6.5 years of follow-up 50 .…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in line with two previous studies in adults in their 30s, which also did not find any relationship between adherence to the MIND diet and reduced risks of stress, anxiety and depression. 48,49 However, a prospective cohort study in adults in their late 70s found that the MIND diet score was associated with lower rates of depression over a 6.5 years of follow-up. 50 More studies are clearly needed to evaluate the true association between the MIND diet and mood, possibly on different age groups.…”
Section: Papermentioning
confidence: 99%
“…The aforementioned limitations in addition to the various questionnaire used for anxiety assessment, State and Trait Anxiety Inventory (STAI), might have led to such inconsistency. Also, in a cross-sectional study evaluating the association between adherence to the MIND diet, sleep quality, and mental health no significant associations were found between the odds of anxiety, depression, and the MIND diet; however, Greater adherence to this dietary pattern had led to lower odds of poor sleep quality and sleep-related outcomes [ 41 ]. The contradictory results can be ascribed to the study population, exclusively males, and the different questionnaires, 21-item depression, anxiety, and stress scale (DASS-21), applied for anxiety assessment.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study in 810 very old adults over the age of 85 years showed that those with a "good" self-reported sleep quality had a "moderateto-high" diet quality, even after adjustment for several confounding factors [72]. Another paper by Godos et al [73], as part of the Mediterranean healthy Eating, Ageing, and Lifestyle (MEAL) study, documented that a diet with a higher Dietary Inflammatory Index (DII ® ) brought a higher risk of inadequate sleep quality in adults, as assessed by the PSQI questionnaire, while Rostami et al, using the same sleep quality questionnaire, recently found that adherence to the Mediterranean-DASH Intervention for Neurodegenerative Delay (MIND) Diet brought a lower risk of poor sleep quality in adults [74].…”
Section: Discussionmentioning
confidence: 99%